Efficacy And Safety of Sacral Neuromodulation in the Treatment of Females with Refractory Idiopathic Non-Obstructive Urinary Retention - Ismail, Mohammed Bassil; Abdullhussein, Wameedh; Alwaeli, Hayder (Urology Journal, 2026)
Purpose: Non-obstructive urinary retention (NOUR) is the inability to empty the bladder with no physical obstruction to urine flow. It can occur as a result of neurological disorders or be idiopathic. In younger women, it may be caused by Fowler’s syndrome (FS), a rare disorder in which the urethral sphincter fails to relax to allow urine to pass normally. This study covers both idiopathic NOUR and FS. Sacral neuromodulation (SNM) has been introduced as an effective option for patients with NOUR. Materials and Methods: Forty-two patients (aged 17 to 61 years) suffering from refractory NOUR who had a successful first-stage SNM with the Interstim II device, and in whom the second stage was completed, were prospectively studied in the department of neurogenic bladder and neuromodulation in our hospital from February 2016 to August 2019 to evaluate the efficacy and safety of SNM. Results: The study included forty-two women with NOUR: 20 (47%) with FS and 22 (53%) with idiopathic NOUR. Their mean age was 27.2 ± 12.4 years. Thirty-eight (90%) of them had a successful trial phase (responders) with more than 50% improvement in their voiding parameters. After continued follow-up, a clinical success rate of 79% (30 out of 38 cases) was achieved, with a median follow-up period of 28 ± 8 months. The voiding parameters of these 38 patients showed statistically significant improvement after SNM. Their post-void residual volume dropped significantly from 330 ± 77 mL to 97 ± 55 mL (P < 0.001), average voided volume increased from 60 ± 23 mL to 265 ± 99 mL (P < 0.001), and the number of clean intermittent catheterizations per day fell from 5.6 ± 1 to 1.3 ± 1.6 (P < 0.001). The total number of patients who required surgical revision was 10 (26.4%), for reasons including malfunction due to external trauma in four patients (10.5%), continuous pain in four (10.5%), and device infection in two (5%). Conclusion: SNM is an effective and safe option for women with refractory idiopathic non-obstructive urinary retention and Fowler's syndrome.